Characterization of TcCAL1: A calcium binding protein and its role in the life cycle of Trypanosoma cruzi - Rodríguez Durán, Jessica Jenireth (2022)
In Trypanosoma cruzi, several studies have reported that intracellular calcium (iCa2+) levels increase duringmetacyclogenesis and parasite adhesion to host cells. Also, channels that generate variations in iCa2+ concentrationhave been studied. However, most of the proteins that interact with this ion, possibly decodingits signals, have not been characterized. TcCAL1 is a 103 amino acid protein with EF-hand type domainsfor Ca2+ binding, with no known function and specific to kinetoplastids. In this work, we studied the roleof TcCAL1 in some aspects of the parasite life cycle. By western blot, it was demonstrated that TcCAL1is more abundantly expressed in the trypomastigote forms, compared to the amastigote and epimastigotestages. Through immunofluorescence microscopy, it was determined that TcCAL1 is localized throughout thecell body of the three stages mentioned. Also, cultures overexpressing TcCAL1 fused to a six-histidine tag(pTREX/TcCAL1x6His) and cultures containing the empty pTREX vector (controls) were obtained. In metacyclogeneticassays, overexpression of TcCAL1x6His significantly decreased the percentages of differentiationfrom epimastigote to metacyclic trypomastigote forms. When invasion processes were evaluated, overexpressionof TcCAL1x6His caused an increase in the adhesion percentages of metacyclic trypomastigotes to the surfaceof Vero cells, as well as the number of parasites attached per cell. Similarly, the percentages of infected Verocells and the number of intracellular amastigotes per cell increased in cultures overexpressing TcCAL1x6His.However, parasites overexpressing TcCAL1x6His showed similar epimastigote proliferation rates to controls,as well as differentiation of metacyclic trypomastigotes to axenic amastigotes. On the other hand, a yeasttwo-hybrid assay was performed expressing TcCAL1 as bait in conjunction with a T. cruzi cDNA library.As a result, two TcCAL1-interacting proteins were identified, with characteristic armadillo-like or prefoldinlikedomains, respectively. Such interactions were studied by co-immunoprecipitation and mass spectrometry,where a protein with prefoldin domains was also identified. However, no proteins with armadillo domainswere detected. Co-localization by immunofluorescence microscopy of epimastigotes expressing a fragment ofthe armadillo domain protein fused to an HA tag was evaluated using anti-HA and anti-TcCAL1 antibodies.As a result, signal intensity overlap was observed for both antibodies. These results allow us to hypothesizethat TcCAL1x6His limits iCa2+ concentration in the parasite, negatively affecting metacyclogenesis. Also, wepropose that overexpression of TcCAL1x6His promotes the invasiveness of T. cruzi to host cells by activatingsome Ca2+-dependent function. Future studies aim to determine Ca2+ binding to TcCAL1 and to quantifyiCa2+ levels in parasites overexpressing TcCAL1x6His against different components of the extracellular matrix.This study reaffirms the importance of studying uncharacterized proteins exclusive to the parasite to deepenour knowledge of T. cruzi biology.